THE IMPORTANCE OF LITERATURE IN THE FORMATION OF PERSONALITY IN THE FAMILY AND THE INFLUENCE OF GENDER STEREOTYPES ON SOCIAL CONSCIOUSNESS (Universal International Scientific Journal, 2026)
This article highlights the role of parents in raising children in the formation of a mature personality, relying on artistic and spiritual literature. It also analyzes the impact of gender stereotypes on children's minds, social imagination and value systems from a scientific and psychological perspective. The need to raise a child spiritually through the family environment, national heritage and literary sources is substantiated.
Keywords: child rearing, family psychology, literature, gender stereotype, social consciousness, mature personality, spiritual value.